2015
DOI: 10.1111/aas.12568
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of and satisfaction with health care among opioid users with chronic non‐malignant pain

Abstract: Combined with previous findings of high levels of pain in spite of opioid treatment, the present findings indicate that symptomatic relief is not a prerequisite for patient satisfaction. The study shows higher patient satisfaction compared to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Studies were published from 1997 to 2019. Studies were mainly from the United States (n¼33) [10,, with other studies from Australia [54][55][56], Belgium [57], Brazil [58], Canada [59], Chile [60], England [61], Denmark [9,[62][63][64][65][66][67], Germany [68,69], India [70], Iran [71,72], Israel [73], Norway [74], Portugal [75], Spain [76], The Netherlands [77], and/or from multiple countries (France, Germany, Italy, Spain, the UK) [78]. Four studies were from middle-income countries [58,[70][71][72], and no studies were from low-income countries.…”
Section: Included Studiesmentioning
confidence: 99%
“…Studies were published from 1997 to 2019. Studies were mainly from the United States (n¼33) [10,, with other studies from Australia [54][55][56], Belgium [57], Brazil [58], Canada [59], Chile [60], England [61], Denmark [9,[62][63][64][65][66][67], Germany [68,69], India [70], Iran [71,72], Israel [73], Norway [74], Portugal [75], Spain [76], The Netherlands [77], and/or from multiple countries (France, Germany, Italy, Spain, the UK) [78]. Four studies were from middle-income countries [58,[70][71][72], and no studies were from low-income countries.…”
Section: Included Studiesmentioning
confidence: 99%
“…It is with interest that we read the article by Hansen et al, "Consumption of and satisfaction with health care among opioid users with chronic non-malignant pain" published in the June 2015 issue of "Acta Anaesthesiologica Scandinavica". 1 The authors performed a cross-sectional study, using self-reported data from the substudy of health care use in HUNT3. The authors discovered persons with chronic non-malignant pain reported a higher consumption of health care services, increased level of opioid use, and high satisfaction with health care service.…”
Section: Sirmentioning
confidence: 99%